PELATIHAN KEMAMPUAN BERPIDATO BAGI AKTIVIS BEM DAN BLM UNIVERSITAS LANCANG KUNING - Yani, Juli (EDUTECH CONSULTANT, 2017)
Speaking is one form of oral language activities. As a form of oral language, speech concerned with the expression of ideas and reasoning using spoken language that is supported by aspects nonkebahasaan (facial expressions, gestures, eye contact, etc.). Thus the speech is the activity of conveying the idea verbally using proper reasoning and utilizing nonkebahasaan aspects that can support the efficiency and effectiveness of the disclosure of the idea to the people in a particular event.